The Impact of Gamification on Education: How Games are Making Learning More Fun and Effective - Asmuni Asmuni; Qalka Sandi; Hafizul Husni (Education Studies and Teaching Journal (EDUTECH), 2024)
This research presents a systematic review of the impact of gamification elements, such as points, badges, and leaderboards, on learning outcomes and student engagement in educational contexts. Literature analysis shows that the use of gamification in education can increase student motivation, participation and performance. However, there is variation in the effectiveness of gamification elements depending on the context and student characteristics. Implications and future research directions are also discussed.